Associations Between Self‐Reported Weight History and Sarcopenic Obesity in Adults with Knee Osteoarthritis. Issue 2 (24th January 2021) - Godziuk, Kristine; Prado, Carla M.; Woodhouse, Linda J.; Forhan, Mary
Abstract : Objective: The purpose of this study was to examine associations between self‐reported weight history and sarcopenic obesity in adults with advanced knee osteoarthritis (OA). Methods: Self‐reported weight history was collected from n  = 151 adults (58.9% female) with knee OA and BMI ≥30 kg/m 2 in a cross‐sectional study. Body composition was assessed using dual‐energy x‐ray absorptiometry. Sarcopenic obesity was defined as appendicular skeletal muscle mass, adjusted by BMI,  <0.51 kg/m 2 in females and <0.79 kg/m 2 in males; prevalence was 27.2%. Weight gain in the preceding year, weight gain ≥5% of body weight in the past decade, and multiple weight cycling events in life‐span (loss of ≥10 lb [4.5 kg] with regain ≥3 times) were examined using logistic regression (adjusted by age, sex, and %fat mass), with the dependent variable of sarcopenic obesity presence. Results: Weight gain in the preceding year was associated with sarcopenic obesity (odds ratio [OR]: 2.45, 95% CI: 1.02‐5.87). No associations were found with weight gain in the past decade (OR: 1.04, 95% CI: 0.43‐2.5) or weight cycling (OR: 0.86, 95% CI: 0.37‐2.01). Conclusions: In adults with obesity and advanced knee OA, self‐reported weight gain in the preceding year was associated with sarcopenic obesity. This patient population may benefit from recommendations that prioritize prevention of weight gain.